Theories of the mind - Priest, Stephen (England Penguin Books, 1991)
Many of the world's leading thinkers have been haunted by the same great philosophical puzzle: What is the exact relationship between the body and the mind? In lucid prose, Priest walks readers through the main schools of philosophical thought--from Plato and Descartes to the dualists, double aspect theorists, and phenomenologists--and offers a compelling new solution.